Impact of Anchor Drag on Subsea Pipeline Integrity: Numerical Study on Crack Propagation and Leakage - Arianta, Arianta; Tawekal, Ricky Lukman; Santoso, Jason Filius; Ilman, Eko Charnius (Civil Engineering Dimension, 2026)
Anchor drag incidents impacting subsea pipelines lead to structural failure, driven primarily by crack propagation under mechanical stress. This study employs finite element modelling (FEM) and the extended finite element method (XFEM) to evaluate how initial crack dimensions (depth: 4–6 mm; length: 20–60 mm) affect pipeline integrity. Results indicate that pipelines with smaller initial cracks (4 mm depth) resist leakage until an anchor drag distance of 67.839 m, whereas larger cracks (6 mm depth) fail at 33.389 m, emphasizing crack depth as the critical factor in reducing structural resilience. Crack propagation follows a triphasic pattern: slow initiation, rapid acceleration at 25–35 m drag distance, and deceleration near the pipe wall. Larger cracks propagate faster, with 6 mm depth cracks reaching critical failure earlier than smaller defects.